RESTORATIVE JUSTICE AND FULFILLMENT OF VICTIMS' RIGHTS IN HANDLING DOMESTIC VIOLENCE CASES (Study at the Deli Serdang District Attorney's Office) - Veryanto Sitohang; Andi Maysarah; Dian Hardian Silalahi (NOMOI Law Review, 2026)
Domestic violence cases present a complex legal challenge where rigid retributive punishment often exacerbates the economic vulnerability of victims. This study aims to evaluate the implementation of restorative justice at the Deli Serdang District Attorney's Office and its effectiveness in ensuring the fulfillment of victims' rights. Employing an empirical juridical method through interviews and case analysis, this research assesses the application of Prosecutor’s Regulation Number 15 of 2020. The results demonstrate that the prosecutor's office successfully utilizes mediation to secure immediate economic restitution and preserve family unity, offering a superior pragmatic alternative to incarceration. However, the analysis reveals a critical deficiency: the current practice prioritizes material compensation and administrative efficiency, frequently overlooking long-term psychological recovery and safety guarantees due to the absence of mandatory professional risk assessments. The study concludes that while beneficial for economic stability, the current mechanism requires refinement. Consequently, it suggests an ideal model integrating psychosocial evaluations and strict post-agreement monitoring to ensure substantive justice and genuine protection.